Moral vision in the Histories of Polybius - Eckstein, Arthur M. (Hellenistic culture and society, 1995)
Arthur Eckstein's fresh and stimulating interpretation challenges the way Polybius' Histories have long been viewed. He argues that Polybius evaluates people and events as much from a moral viewpoint as from a pragmatic, utilitarian, or even "Machiavellian" one. Polybius particularly asks for "improvement" in his audience, hoping that those who study his writings will emerge with a firm determination to live their lives nobly. Teaching by the use of moral exemplars, Polybius also tries to prove that success is not the sole standard by which human action should be judged.